Conservation of banana pollen: The progress of activities referring to the approved milestones - Panis, Bart (2025)
Presentation at the First Annual Meeting of Banana project INV-040974 entitled “Collection, Characterization and Pre-breeding of Wild Banana”, 11 Febr, 2025, BRIN, Cibinong, Indonesia